INCREASING THE READING INTEREST OF PANOHAN ELEMENTARY SCHOOL STUDENTS BY USING THE READING CHALLENGE METHOD - Muhamad Mujib; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
PThis study aims to increase students' reading interest by using the Reading Challenge method in fourth grade students of SD Negeri Panohan. This study used 8 students as subjects from class IV SD Negeri Panohan. The research conducted in this research is classroom action research by applying the stages of planning, observation and reflection. The research started from the pre-cycle, the first cycle, and the second cycle. Data from the results of the student response questionnaires were analyzed quantitatively and the data from the observations were analyzed qualitatively. From the results of the study showed that in the first cycle the percentage of student questionnaire results obtained an average value of 71.82%, then in the second cycle it can be seen that there is an increase in the average value of the student questionnaire results by 87.14. From the results of the analysis, it can be concluded that the Reading Challenge method can increase the reading interest of fourth graders at SD Negeri Panohan.